-8(r+9)-7=9

Simple and best practice solution for -8(r+9)-7=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(r+9)-7=9 equation:


Simplifying
-8(r + 9) + -7 = 9

Reorder the terms:
-8(9 + r) + -7 = 9
(9 * -8 + r * -8) + -7 = 9
(-72 + -8r) + -7 = 9

Reorder the terms:
-72 + -7 + -8r = 9

Combine like terms: -72 + -7 = -79
-79 + -8r = 9

Solving
-79 + -8r = 9

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '79' to each side of the equation.
-79 + 79 + -8r = 9 + 79

Combine like terms: -79 + 79 = 0
0 + -8r = 9 + 79
-8r = 9 + 79

Combine like terms: 9 + 79 = 88
-8r = 88

Divide each side by '-8'.
r = -11

Simplifying
r = -11

See similar equations:

| xe^(-t)*(dx)/(dt)=t | | 10=3x+-5 | | 250m^3+54= | | m+5=-5m+5 | | (1+4x)+137=x | | 15-1/2b--3 | | 9+-8p= | | x^3-5x^2=4x | | (6x+4)+136=x | | -4x+-2= | | y-2/3=2-y/5 | | 4x-2+4x=4x+9+2x | | X+(n+6)=4n | | 12.06=-4x | | (d^3-6d^2+13d)y=0 | | .6x-5=.2x+7 | | -2(-5x+2)=5(9-2x) | | 4.2=5x | | 5x-8=17.5 | | 5/8x7/12 | | -8=-(m-8) | | X(x+30)=180 | | 1a-1/a^2-9a | | -88=-(m-8) | | -3(5t-5)+6t=8t-9 | | x+2x=x+70 | | 46=-16t^2+46+6 | | -3(-x)= | | h=-16t^2+46+6 | | 2x^2=4+7x | | -20=-4m-6m | | 6x^2+8x^2=26x^3 |

Equations solver categories